Enhancing Students’ Learning Outcomes in Science and Social Studies through the Inquiry-Based Learning Model in Grade V Elementary School - Selpianti, Selpianti; Zulnuraini, Zulnuraini; Khairunnisa, Khairunnisa; Aras, Nurul Fitria; Wilade, Surahman (Journal of Innovation and Research in Primary Education, 2025)
Despite the integration of Science and Social Studies (IPAS) under Indonesia's Kurikulum Merdeka, classroom practices remain predominantly teacher-centered, resulting in low student engagement and inadequate achievement of minimum mastery criteria. This study examined the effectiveness of inquiry-based learning in addressing these pedagogical challenges. Employing a classroom action research design, this study was conducted with 28 fifth-grade students at SD Inpres 3 Tondo, Palu, across two iterative cycles. Data were collected through systematic classroom observations using structured protocols and achievement tests validated through expert review (content validity index = 0.89, KR-20 reliability = 0.82). Analysis examined teacher instructional quality, student engagement patterns, and learning outcomes across cycles. Implementation of inquiry-based learning produced substantial improvements across all measured dimensions. Teacher instructional quality advanced from 70% to 90%, while student engagement increased from 59% to 75%. Most notably, classical learning mastery improved dramatically from 78% in Cycle I to 96% in Cycle II, with classical absorption rising from 74% to 89%, indicating significant conceptual understanding gains. Inquiry-based learning effectively enhances IPAS learning outcomes by fostering active participation, critical thinking, and collaborative knowledge construction. These findings validate inquiry pedagogy as a viable approach for implementing integrated curriculum within Indonesian elementary education, providing empirical support for constructivist learning principles in authentic classroom contexts.